Lenin and the Russian revolution - Hill, Christopher (Harmondsworth : Penguin Books, 1971)
Bibliotheek François Vercammen
Engels
Monografie
Keywords: Lenin, Vladimir; Russische revolutie; Sovjet-Unie.